Genetic Diversity in Cultivated Common Bean: II. Marker-Based Analysis of Morphological and Agronomic Traits - Singh, Shree; Gutiérrez, J.A.; Molina, A.; Urrea, C. (Wiley, 1991)
Knowledge of patterns of genetic diversity enhances the efficiency of germplasm conservation and improvement. This study examined the organization of diversity for morphological and agronomic characteristics in 306 landraces of cultivated common bean (Phaseolus vulgaris L.) from Latin America and its relationship with phaseolin seed protein and allozyme diversity of the landraces. Data on pigmentation, growth habit, and leaflet, pod, seed, and phenology traits, as well as reaction to four important diseases and an insect pest, obtained from field evaluations at three locations in Colombia during the 1987-1988 cropping season, were analyzed by multivariate statistical analyses. In addition, these same 306 landraces were characterized by electrophoresis for phaseolin seed protein and nine allozymes. Results permitted separation of these landraces into Mesoamerican and Andean groups, confirming prior phaseolin and allozyme data. A marker-based multivariate analysis, using phaseolin or allozymes as an initial classification criterion, followed by a corroborating analysis of morpho-agronomic traits, suggested the existence of subgroups within each of the major Andean and Mesoamerican groups, with distinctive morphology, adaptation, and disease resistances. Molecular analyses in conjunction with morphological and agronomic evaluations of gene bank accessions are recommended, because these provide complementary information and increase the resolving power of genetic diversity analyses.